Turkish nursing students’ compliance to standard precautions during the COVID-19 pandemic - Sevcan Topçu; Zuhal Emlek Sert (PeerJ, 2023)
Objectives The aim of this study was to assess nursing students’ compliance to standard precautions during the COVID-19 pandemic. Methods A cross-sectional study was conducted from December 2021 to June 2022, 816 nursing students participated in the study. A socio-demographic questionnaire and Compliance with Standard Precautions Scale were used to collect data. Means and percentages were used to report socio-demographic characteristics multiple regression analysis used to identify the factors influencing compliance with standard precautions. Results The mean age of nursing students was 21.30 ± 1.31 years. The majority of nursing students were female, with 703 (86.2%) being female and 113 (13.8%) being male. Compliance among nursing students was 76.8% overall. Nursing students reported the highest compliance (97.7%) with putting used sharp articles into sharp boxes, with 97.1% compliance for covering mouth and nose when wearing a mask. Participants reported the lowest (38.6%) when it came to not recapping used needles after giving an injection. Regression analysis revealed that gender, year of study, and having needlestick injury or contact with blood/body fluids experience all influenced nursing students’ compliance with standard precautions. Conclusions During the pandemic, nursing students compliance to standard precautions was optimal, according to this study. More research should be done to assess nursing students’ compliance with standard precautions and the effect of infection control strategies used to prevent COVID-19 transmission.